Some remarks on the idea of the foreign law application - Belović, Jelena (Sociološki pregled, 2021)
The evolution of the idea of the foreign law application is connected to the work of post-glossators in the 14th and 15th centuries. The aim of this paper is to present the roots of the idea, but also to point out the social circumstances enabling its development. Today’s indisputable justification of the foreign law application has been advocated and criticized through various arguments for centuries. The chronological presentation requires the application of the historical law method, while the comparative method is necessary in analyzing comparative law solutions. The foreign law application is dictated by the requirement for observing legitimate interests of others that is aimed at reciprocal action. In the age of globalization and increased interaction in social relations, the application of foreign law is a regular occurrence. However, in certain terms, the global and regional unification of legal regulations could be seen as the negation of the foreign law application.
Keywords: particularity; unification; foreign law application; private international law